Assessment of Yoruba Language Teachers’ Utilization of Evaluation Instruments in Grading Students - J.A, Abijo (European Scientific Journal, ESJ, 2016)
The study assessed Yoruba language teachers’ utilization of evaluation instruments in grading students.Using multistage sampling procedure, one hundred Yoruba language teachers who teach senior secondary classes two and three were randomly selected from 75 schools in three states of Nigeria (Oyo, Osun and Ekiti). Data were analysed using descriptive (frequency count and percentages) and t-test statistics. Result indicates that Yoruba language teachers adopt the multiple choice test and a combination of essay and objective tests in that order to grade students. Other evaluation instruments used and listed in order of utilization are oral test, practical work, submitted homework and student’s notes. Evaluation instrument that encourage higher thinking such as practical work and submitted home work are never or less often used respectively. In terms of group differences in the utilization of these instruments, findings show that the utilization of the multiple choice test is sensitive to teacher experience and professional status. This implies that teachers with more experiences (6 years and above) and those with professional training use multiple choice tests more frequently. Also, there is no statistical significant difference between male and female utilization of evaluation instruments. It was thus recommended that Yoruba language teachers should be exposed to training and re-training programme on the importance of using practical class activities and using of submitted home work for students as an evaluation instrument in grading Yoruba language students in schools.